Pengaruh Kepercayaan Konsumen pada Ulasan Food Vlogger dan E-wom terhadap Keputusan Pembelian Kuliner di Surabaya - Jasmine Aszahra; Reiga Ritomiea Ariescy (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The rapid development of social media has changed the way people obtain information about culinary experiences. Reviews delivered by food vloggers often become a reference; however, issues related to consumer trust arise because the content is often in the form of paid promotions, making it perceived as less objective. On the other hand, electronic word of mouth (e-WOM), which is based on users direct experiences, is considered more neutral and trustworthy. This study aims to analyze the influence of consumer trust in food vlogger reviews and e-wom on culinary purchase decisions in Surabaya. This research employs a quantitative method with an explanatory approach. The instrument used is a questionnaire distributed online. The sample consists of 100 respondents selected using purposive sampling based on predetermined criteria. The data were analyzed using Structural Equation Modelling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results of this study indicate that consumer trust in food vlogger reviews has a positive but not significant effect on purchase decisions, while electronic word of mouth has a positive and significant effect on purchase decisions.